Private Security Companies in Kenya and the Impact of Chinese Actors - Shuwen Zheng; Ying Xia (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
Researchers Shuwen Zheng and Ying Xia use Kenya as an active case study to explore the development and impact of Chinese private security companies (PSCs). As a whole, the private security sector is in a boom period – but how are Chinese actors faring in this growth? Join Zheng and Xia as they delve into the nuances involved in the sustainability of Chinese PSCs and conclude with several recommendations for how Chinese actors can adjust to flourish in the private security sector.
Keywords: 330